Polyfunctionality and distribution of reflexive verbs in Latvian - Kalnača, Andra; Lokmane, Ilze (Baltistica, 2016)
The aim of the current paper is to analyze Latvian reflexive verbs from the point of view of their polyfunctionality and distributon.The polysemy of the reflexive verbs is not usually disucussed in the connection with its distribution pattern in the sentence either. This can be partly explianed by the fact that the reflexive verb can have some non-standard language meanings, which following the established practice of the traditional grammars and sometimes even dictionaries,  were not depicted in the language system description either. So the current paper is an attempt to analyze the polyfunctionality of reflexive verbs in connection with their semantic and syntactic functions, without judging the language use from the normative point of view.The classification of Latvian reflexive verbs is based on the relationship between semantic roles and syntactic structure according to the principles devised by Palmer (1994) and Saeed (1997).One and the same reflexive verb may have different lexical meanings with a different distribution for each of the meanings. One and the same verb can belong to different subclasses of the subject and object (or impersonal) verbs.Some reflexive verbs have evaluative or aspectual (iterative) meanings. The evaluative meanings usually are manifested by a positive or negative assessment of the event (the context can be enhanced by the adverbs good or bad) and the consequences while the aspectual meaning is manifested by the intensity of the action, that is – iterativity.The study confirms the assumption that reflexive verbs are independent lexemes as opposed to non-reflexive verb forms. Each reflexive verb has its distinct semantic system and distribution which is different from polysemy of non-reflexive verbs and their distribution. The system of reflexive verbs in Latvian is open where new meanings and even new reflexive verbs arise particularly in colloquial use.